Confirming the occurrence of two fiddler crabs, Tubuca dussumieri (H. Milne Edwards, 1852) and T. coarctata (H. Milne Edwards, 1852) (Crustacea: Decapoda: Ocypodidae), in Hong Kong by DNA barcoding and morphology - Jimenez, Pedro Julião; Chang, Kai; Shih, Hsi-Te; Yasuhara, Moriaki (Zootaxa, 2024)
The Indo-West Pacific region has a rich fiddler crab fauna. In East Asia, some species of fiddler crabs, such as Tubuca coarctata (H. Milne Edwards, 1852) and T. dussumieri (H. Milne Edwards, 1852), are considered insular, being present in the Philippines, Taiwan, and Ryukyus, but with no consistent record on continental China. Although T. dussumieri has been previously recorded in continental China, these records were considered dubious or misidentified. The nature of the Kuroshio Current and the colder waters of the China Coastal Current, compared to the currents along the eastern coasts of the Philippines and Taiwan, are considered barriers to the entrance of larvae of these species into the region. Nonetheless, using the cytochrome oxidase subunit I (COI) gene and morphological evidence, we present the first record of T. coarctata and show the presence of a T. dussumieri population in Hong Kong SAR, China. We hypothesize that the newly found T. coarctata in Hong Kong may be related to water temperature increases due to anthropogenic climate change, which allows its larvae to survive in this region and develop into adult crabs. Furthermore, our findings corroborate previous records of T. dussumieri in continental China. The restricted distribution of T. dussumieri in China and the smaller size of individuals, however, may indicate suboptimal habitats for arriving larvae. The limited presence of the two crabs on Chinese shores indicates that the intense coastal development in the country, such as in Hong Kong, may destroy suitable habitats and render these species susceptible to local extinction.